1996
DOI: 10.2307/3096952
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Home Ownership and Housing Quality, 1991

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 52 publications
(35 reference statements)
1
61
0
Order By: Relevance
“…Accordingly, the purchase of a home and the growth of housing equity is considered to result from the greater incomes and needs for space that accrue as individuals get older, marry, and have children. Many studies have found that age, education, income, and marriage are strongly associated with homeownership and the value of owned housing (e.g., Alba and Logan 1992;Coulson 1999;Krivo 1995;Lewin-Epstein et al 1997;Lewin-Epstein and Semyonov 2000;Rosenbaum 1996). Yet, they have also shown that the economicllife-cycle approach provides an incomplete explanation of racial and ethnic differences in rates of homeownership and net housing worth in the United States.…”
Section: Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the purchase of a home and the growth of housing equity is considered to result from the greater incomes and needs for space that accrue as individuals get older, marry, and have children. Many studies have found that age, education, income, and marriage are strongly associated with homeownership and the value of owned housing (e.g., Alba and Logan 1992;Coulson 1999;Krivo 1995;Lewin-Epstein et al 1997;Lewin-Epstein and Semyonov 2000;Rosenbaum 1996). Yet, they have also shown that the economicllife-cycle approach provides an incomplete explanation of racial and ethnic differences in rates of homeownership and net housing worth in the United States.…”
Section: Prior Researchmentioning
confidence: 99%
“…However, this research has focused primarily on analyses of either residential segregation or inequality in homeownership, not on the sources of differences in the accumulation of equity across groups (Alba and Logan 1992;Alba et al 2000b;Krivo 1995;Krivo and Kaufman 1999;Massey and Denton 1993;Rosenbaum 1996). This work is informative regarding the sources of inequality in equity because the transition to homeownership is a prerequisite to holding any wealth in a home.…”
Section: Prior Researchmentioning
confidence: 99%
“…1992; Jackman and Jackman 1980;Krivo 1986;Long and Caudill 1992;Megbolugbe and Cho 1996;Myers and Chan 1995;Parcel 1982;Rosenbaum 1996;Sykes 2003;Wachter and Megbolugbe 1992). In response, researchers have increasingly turned their attention to the ways in which social context structures minority homeownership attainment.…”
mentioning
confidence: 99%
“…The effectiveness of the compensation policy for quitting rural residential land is also affected by migrant workers' individual resource endowment. Moreover, the endowment effect radiated by migrant workers' personal and household resource endowment on the compensation policy for quitting rural residential land has a direct influence on their willingness to buy houses in cities [8,9]. This study is expected to help set up an alternative compensation mechanism for quitting rural residency based on individual resource endowment, and examine the effect of the compensation policy for quitting rural residential land on migrant workers' willingness to buy houses in cities and the differences of migrant workers' willingness to buy houses in cities under the guide of the compensation policy, according to their individual endowment and the policy actually implemented by the local government.…”
Section: Introductionmentioning
confidence: 99%